Case‐based discussion: perceptions of feedback. (12th April 2017) - Mohanaruban, Aruchuna; Flanders, Lucy; Rees, Huw
Summary: Background: Over recent years there has been a trend towards developing high‐quality assessments to assess a doctor's performance in the workplace. Case‐based discussion (CbD) is a form of workplace‐based assessment that has the potential to provide feedback to trainees on their performance or management of a specific case. The aim of this study was to explore how CbDs are perceived and implemented in practice amongst a UK cohort of medical trainees. Methods: This study involved 78 medical trainees at a UK hospital completing a questionnaire rating their last CbD experience, including the duration spent receiving feedback, whether it was pre‐planned or ad hoc and how they responded to the feedback received. Focus groups were conducted involving 12 trainees to discuss common themes on feedback arising from the questionnaire, and thematic analysis was carried out following these discussions. Results: Only 19 per cent of assessments were pre‐planned and the average duration of assessments was 6–10 minutes, with feedback lasting less than 5 minutes. A total of 76 per cent of trainees responded to the feedback they received by completing self‐directed learning or by addressing the specific action points arising from the feedback. The focus groups highlighted the barriers to incorporating these assessments into everyday practice, including appreciating the time constraints and the importance of trainer engagement in the assessment process. The aim of this study was to explore how CbDs are perceived and implemented in practice Conclusion: This study demonstrates that most trainees appreciate the educational value of CbDs, but more emphasis and training is required in planning these assessments and in providing feedback that is both specific and actionable.